Investigating Indonesian Beauty Contest Instagram Posts Sparking Feminism - Henny Merizawati; Andini Anugrah Fitria; Feny Martina (UNIB Press, 2023)
In a patriarchal country like Indonesia, feminism is still an extremely relevant movement that needs to be manifested to improve women's life. Social media has become the most effective platform to promote the idea of feminism. Nowadays, women have crucial roles during the COVID-19 pandemic such as a working women community participating in the digital age. Many other feminists or woman-related communities, such as beauty pageant groups, contribute to spreading the pandemic awareness using their media while displaying their feminist perspective. Relevant to these issues, this study intends to uncover how women are represented on a beauty pageant social media account during the COVID-19 era to exhibit how the feminism ideology is presented through the women’s representation. This study focuses on analyzing the pictures from the Puteri Indonesia Instagram account (@officialputeriindonesia) posted during the pandemic by employing Kress and van Leeuwen's social semiotics theory of visual grammar complemented by the Critical Discourse Analysis (CDA) method. Results of the study denote that women represent their roles day by day by posting their images while conducting various activities such as social, environmental, cultural and health activities in well-dressed outfits. Women are also portrayed as possessing various characteristics that challenge the patriarchal stereotypes. Furthermore, these indicate the positive portrayal of feminism that concerns giving women more chances to be independent of the stereotypes and be more engaged in various roles regardless of gender.